The Disability Pay Gap Within and Across Firms - John Forth; Melanie K. Jones (Institute of Labor Economics (IZA), 2025)
We assess the extent to which the UK disability pay gap is a consequence of the distribution of workers across firms and within-firm disability pay gaps. We do so by applying decomposition methods to newly-linked data which matches high quality information from employer payroll records to Census data on disability. Our findings indicate that the distribution of disabled and non-disabled employees across firms acts to reinforce within-firm disability-related pay inequality in England and Wales. However, both the disability pay gap and unexplained disability pay gap predominately exist within rather than between firms, supporting the introduction of employer disability pay gap reporting in the UK.
Keywords: J31; J71; 330; disability pay gap; wage discrimination; linked employer-employee data